The Mystical Self between Annihilation and Deification: Cusanus as Interpreter of Dionysius the Areopagite - Colizzi, Paolo (Studies in spirituality, 2025)
In De visione Dei, Nicholas of Cusa reinterprets Dionysian mystical theology in a way that both preserves and transforms its apophatic core. God remains ineffable, a superluminous darkness beyond all conceptual grasp. Yet this divine unknowability does not entail the annihilation of the self, as in Dionysius’ mystical union. Instead, the encounter with God becomes for Cusanus the path by which the soul discovers itself as the image of the Ineffable. Individuality – marked by perspective, difference, and creative power – is not something to be overcome, but the very medium of divine manifestation. In this way, Cusanus lays the groundwork for a Renaissance anthropology rooted in Neoplatonic metaphysics, yet centered on the individual, creative human being. The divine shines not despite human limitation, but precisely through it.